2006
DOI: 10.1111/j.1525-1438.2006.00573.x
|View full text |Cite
|
Sign up to set email alerts
|

The utility of presurgical CA125 to predict optimal tumor cytoreduction of epithelial ovarian cancer

Abstract: The objective of this study was to evaluate the ability of a preoperative serum CA125 to predict whether optimal debulking (OD) could be achieved for patients with stage III and IV epithelial ovarian cancer (EOC). The records of consecutive patients who underwent primary surgery for EOC at Indiana University Hospital between January 1997 and January 2003 were reviewed. Eligibility criteria included FIGO stage III/IV disease, surgery by gynecologic oncology faculty, preoperative CA125, and an operative note cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 26 publications
3
22
0
2
Order By: Relevance
“…Preoperative serum CA125 has been reported to correspond to PDS outcome 16,[30][31][32] although contradictory results have also been presented. 10,33 Perioperative CA125 changes have also been associated with PFS. 34 Our previous study focused on HE4 in NACT response evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative serum CA125 has been reported to correspond to PDS outcome 16,[30][31][32] although contradictory results have also been presented. 10,33 Perioperative CA125 changes have also been associated with PFS. 34 Our previous study focused on HE4 in NACT response evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…The role of perioperative CA-125 is not fully determined. Some authors could demonstrate a correlation between preoperative CA-125 and surgical outcome, but there have been conXicting results (Barlow et al 2006;Chi et al 2000;Vorgias et al 2009;Kang et al 2010). This study was designed to analyze the potential prognostic impact of CA-125 concentration before and after primary surgery as well as its perioperative variation in a large and homogeneous single-center cohort.…”
Section: Introductionmentioning
confidence: 93%
“…The first one, from Gemer et al, 15 showed at a threshold of 400 U/mL an accuracy of 0.62, and the authors concluded that the clinical applicability is limited. Barlow et al 16 showed similar results at the cutoff of 400 U/mL. Two actual studies provided controversial results.…”
Section: Serological Modelsmentioning
confidence: 88%